MENUJU PARADIGMA ILMU PEMERINTAHAN FORMAL DAN INFORMAL - Adfin Rochmad Baidhowah (Jurnal Politik Pemerintahan Dharma Praja, 2026)
Government studies have been dominated by perspectives that place formal state institutions as the primary actors in meeting societal needs. Although recent literature has shifted attention toward collaborative governance, empirical and conceptual research that systematically explains how formal and informal institutions interact to shape public solutions remains limited, particularly in the context of developing countries like Indonesia. This creates a research gap in understanding government and society relationships, the normative core of governance studies. This article aims to fill this gap by analyzing the relationship between formal and informal institutions in the implementation of local government functions namely service delivery, development, and empowerment, and explaining its implications for the development of a more contextualized government science. Theoretically, this study uses the formal and informal institutional framework developed by Helmke and Levitsky as the primary analytical tool, expanding the typology of formal and informal relations by identifying additional patterns that are empirically relevant in Indonesia. The research method used is archival research, analyzing classic and contemporary literature on government, as well as empirical studies and policy documents related to local government practices in Indonesia. The analysis is conducted thematically and conceptually to synthesize global theory with local phenomena. The results of the discussion indicate that the relationship between formal and informal institutions in Indonesian local governments is not a single entity, but rather varies across five patterns, namely complementary, substitutive, accommodative, competitive, and delegative. This finding confirms that meeting community needs is the result of relational practices between the state and society, thus necessitating the study of governance beyond the formal and informal dichotomy toward a more integrative and reflective analytical framework.